Convergência entre gamificação e metodologias ativas: ferramentas no ensino de anatomia humana - Morano, Domingos Antônio Clemente Maria Silvio (2021)
Active methodologies are student-centered methods based on their prior knowledge and instigating their curiosity and creativity in order to promote meaningful learning. Among these methodologies we have the Time Based Learning (TBL), the board games and gamification that are valuable tools as active methodologies in the teaching and learning processes of Anatomy. Based on these premises, the objective of this work was to identify whether I use active methodologies associated with TBL and Kahoot promoted significant learning. An exploratory, descriptive, almost experimental study was carried out with a quantitative approach in the discipline of human anatomy. To assess learning, a board game, TBL and Kahoot were applied as a gamification tool. The research participants were evaluated before, after the activities were carried out and six months after the Kahoot activities and board games. There was a statistically significant difference in learning after using the board game. It was found that the interviewees reported that the games associated with TBL help to fix the content and that facilitate the learning of anatomy. It was observed that the gamification strategy promoted significant learning when compared to traditional teaching. Regarding long-term learning, it was observed that even after six months of carrying out the activities, students retain long-term knowledge. Regarding the retention of this knowledge, it was found that the kahoot performed six months after the post-test that the students on the topics discussed: bones and joint when compared to the pre-test showed a statistically significant difference (p <0.0001) . Note that even after six months, students retain knowledge. significant. It was found that kahoot, board games and TBL are strategies that promote significant learning in the short and long term and that the use of these active methodologies such as board games and kahoot works as a multimodal tool in the construction of anatomical knowledge, promoting dynamic learning, playful and significant, it was concluded that in relation to the positive aspects, the use of the game promoted significant learning by improving the numbers of correct answers and anatomy learning.